KINERJA PEGAWAI DILIHAT DARI KEMAMPUAN KERJA, DISIPLIN KERJA DAN TEAM WORK PADA PEGAWAI DINAS KESEHATAN KABUPATEN PEMALANG - Ririn Nurhayati; Sri Suprapti (FEB UNTAG Semarang, 2019)
This study aims to determine the effect of work ability on the performance of employees of the Pemalang District Health Office. To determine the effect of work discipline on the performance of Pemalang District Health Office employees. To determine the effect of team work on the performance of employees of the Pemalang District Health Office. Based on this, the research is entitled